Empirical study on international commercial mediation and conciliation - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2014)
In this post on the Kluwer Mediation Blog, the preliminary results from the empirical study on international commercial mediation and conciliation are presented.